Localisation of cyclooxygenase 1 and cyclooxygenase 2 inHelicobacter pylori related gastritis and gastric ulcer tissues in humans. Issue 6 (1st June 2000) - Tatsuguchi, A; Sakamoto, C; Wada, K; Akamatsu, T; Tsukui, T; Miyake, K; Futagami, S; Kishida, T; Fukuda, Y; Yamanaka, N; Kobayashi, M
Abstract : BACKGROUND: Prostaglandin endoperoxide synthase/cyclooxygenase (COX) is the key enzyme in gastric mucosal protection and repair but its cellular localisation in the human stomach is still unclear. AIMS: To investigate immunohistochemically the cellular distribution of COX-1 and COX-2 proteins in the human stomach with or without gastritis or ulceration. PATIENTS AND METHODS: Tissues were obtained by surgical resection of gastric ulcers associated with perforation (n=9) or by biopsy from Helicobacter pylori positive patients with gastric ulcers (n=45) and H pylori negative healthy subjects (n=15). COX expression was detected by semiquantitative reverse transcription-polymerase chain reaction (RT-PCR), western blotting, and light and electron microscopic immunohistochemistry. RESULTS: COX-2 mRNA and protein were detected in gastric ulcer tissues but not in intact gastric mucosa. COX-1 mRNA and protein were detected in the intact mucosa. COX-2 immunostaining was exclusively localised in macrophages and fibroblasts between necrotic and granulation tissues of the ulcer bed. The percentage of COX-2 expressing cells was significantly higher in open than in closed ulcers, and in gastritis than in gastric mucosa without H pylori infection. COX-1 immunoreactivity localised in lamina propria mesenchymal cells was similar in various stages of ulcer disease and in intact gastric mucosa. Electron microscopic immunohistochemistry revealed both COX-1 and COX-2 on the luminal surfaces of the endoplasmic reticulum and nuclear envelope of macrophages and fibroblasts. CONCLUSIONS: Our results showed that COX-2 protein was induced in macrophages and fibroblasts in gastric ulcers and H pylori related gastritis, suggesting its involvement in the tissue repair process.